Antimicrobial and Antibiofilm Potential of Acyclic Amines and Diamines against Multi-Drug Resistant Staphylococcus aureus - Kaur, Gurmeet; Balamurugan, P.; Vasudevan, Sahana; Jadav, Saikiran; Princy, S. A. (Frontiers in Microbiology, 2017)
Multi-drug resistant Staphylococcus aureus (MDRSA) remains a great challenge despite a decade of research on antimicrobial compounds against their infections. In the present study, various acyclic amines and diamines were chemically synthesized and tested for their antimicrobial as well as antibiofilm activity against MDRSA. Among all the synthesized compounds, an acyclic diamine, (2,2’-((Butane-1,4-diylbis(azanediyl)bis(methylene))diphenol) designated asADM 3, showed better antimicrobial activity (MIC at 50 μg/mL) and antibiofilm activity (MBIC50 at 5 μg/mL). In addition, ADM 3 was capable of reducing the virulence factors expression (anti-virulence). Confocal laser scanning microscope analysis of the in vitro tested urinary catheters showed biofilm reduction as well as bacterial killing by ADM 3. On the whole, our data suggest that acyclic diamines, especially ADM 3 can be a potent lead for the further studies in alternative therapeutic approaches.